Studies of Есоtoxicity of Herbicides to Influence the Soil Fauna - Khyzhnyak, Svitlana; Sterlikova, Oksana; Poloschyk, Sergiy; Bulanchuk, Yuliya; Samkova, Oksana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The study of the ecotoxicity of post-emergence and pre-emergence herbicides, which are related to organochlorine pesticides, was carried out. The test objects of the soil fauna were used, since the regulation of the safe use of plant protection products requires an examination of their influence on the soil biota. During the laboratory biotesting the representatives of soil invertebrates – earthworms Eisenia fetida, which play an important role in soil-forming processes, were used as the test object. The changes of the functional status of soil microorganisms (the number of basic taxonomic, ecological, trophic and physiological groups of microorganisms, the biomass of soil microorganisms, the potential nitrification ability of the soil) were also monitored. Differences in the ecotoxicity of herbicides A, CE (active ingredient – acetochlor, 900 g/l) and K, RK (active ingredient – clopyralid, 300 g/l) were revealed in terms of the median lethal concentration (LC50, 14 days) for a representative of soil mesofauna Eisenia fetida and the effects on soil microorganisms. The preparation A (a.i acetochlor) according to a defined value of the median lethal concentration which is 479 mg/kg of substrate (under artificial substrate conditions) for the use of Eisenia fetida is classified as slightly toxic (hazard class III). The obtained results allow to assume the potential ecological risks for the stable functioning of the microbiocenosis with the use of the preparation A (a.i. acetochlor) in conditions of a typical black soil. When using the preparation K (a.i. clopyralid) there is no effect on the survival rate of Eisenia fetida. There are also no significant changes in the quantitative-group composition of the microbial cenosis under conditions of dark gray soil and the typical black soil, no changes in the index of the total biomass of the metabolically active pool of microorganisms and the potential of nitrate accumulation. This indicates its safety in compliance with the recommended application rates. Attention is focused on the high content of the active substance of herbicide A (a. i. acetochlor), compared with K (a.i. clopyralide), its use as an emulsion concentrate, which, along with the proposed high pesticide load, creates potential environmental risks of this preparation for soil fauna.